Analisis Faktor-Faktor Internal Dan Eksternal Terhadap Persaingan Bisnis (Studi Pada Perusahaan Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia 2002 – 2007) - Ardi Hamzah (Universitas Airlangga, 2009)
This research objectives were to analysis the internal and external factors on business competition, both simultaneously and partially. This research done with quantitative approach. The population in this research were food and beverage firms listed in Indonesia Stock Exchanges. This research samples were manufacture firms listed in Indonesia Stock Exchanges period 2002 – 2007. Technique of taking the samples done with purposive sampling, namely firm manufacture have not negative earnings and equity for 2002 – 2007. Analysis technique done with statistic descriptive and examination regression, both simultaneously and partial regression. The result of this research without and with lag showed simultaneously internal and external variables have significant effect on business competition. For partial examination without lag showed human resources and marketing, production and finance (equities) had significant effect on business competition, while finance (liabilities), economic development, and outstanding money amount had not significant effect on business competition. In this matter indicated that human resources, marketing, production and finance especially at equities necessarily concerned related with business competition. For partial examination with lag-1 show human resources, marketing, and finance (equities) had significant effect on business competition, while production, finance (liabilities), economic development and outstanding money amount had not significant effect on business competition. In this matter indicating that human resources, marketing, and finance necessary concerned at future business competition.